MICROGREENS - CURRENT STATUS, GLOBAL MARKET TRENDS AND FORWARD STATEMENTS - Mirela PARASCHIVU; Otilia COTUNA; Veronica SĂRĂȚEANU; Carmen Claudia DURĂU; Ramona Aida PĂUNESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The recent statistical data and market studies have shown that the microgreens market is on a continuously upward trend in Europe and globally due to their healthier and nutritious qualities and for fast adoption of indoor and vertical farming especially in the cities. Worldwide the microgreens become of great interest due to their benefits for people's health and beauty, being 40 times more nutritious than mature vegetables, increasing also the amount of available space that might be put into food production, with environmental benefits and economic profitability. The evolution of microgreens market to its real development potential depends of consumers behaviour and income level. Microgreens are considered 'desert food’ by their huge potential to provide food in marginal areas affected by climate change becoming a part of sustainable farming. The present study pursued the evaluation of microgreens global market trends and forward statements in order to identify them as a potential profitable business in the era of Covid 19 pandemic when farmers should adapt food production to the new economic and social contexts. The study showed an increased consumer interest for “healthy” products, so that the change according to their behaviour shall generate an increase in the microgreens market worldwide.